Long-term contracts in the natural gas industry: Literature survey and data on 426 contracts (1965-2014) - Anne Neumann; Sophia Rüster; Christian von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Long-term contracts are an important element of all economic activity and, thus, critical for understanding modern economic structures. The natural gas industry provides particular insights into the functioning and dynamics of long-term contracts and industry structures, in a sector that is globally important. This Data Documentation provides a survey of the literature on long-term contracts in the natural gas sector, as seen from an institutional and industrial economics perspective; we also add suggestions for further research. The core of the documentation is a detailed database of 426 long-term contracts struck between sellers and buyers between 1965 and 2014. Though not comprehensive, the database covers a large share of contracts, both for pipeline gas and liquefied natural gas (LNG).
Keywords: 330